Covid-19 Transmission Risk Management for Hypertensive Patients in Indonesia - Erwin Purwaningsih (Insights in Public Health Journal, 2021)
Background: Individual behavior in the face of the COVID-19 pandemic is characterized by disruptions or shifts in lifestyle. Covid-19 is more likely to cause extreme symptoms or serious problems in people with some medical conditions (chronic noncommunicable diseases). Hypertension is a non-communicable chronic condition induced by an unhealthy lifestyle. According to data from the national covid-19 distribution map, hypertension is the comorbid condition with the highest number of covid-19 patients. Methods: This study uses a descriptive analysis with a non-experimental framework as its process (cross-sectional). According to the study's goals, research participants used secondary data from the Covid-19 Indonesia distribution map in 2020/2021. Results: The number of confirmed cases is about 10,000 residents in July 2020, and it will continue to rise until May 2021, when it will reach 1,400,000 cases. Hypertension, which accounts for 50.1 percent of covid-19 cases, is one of the most common comorbidities. Diabetes mellitus affects 36.6 percent of people, the heart 17.2 percent, and 10 percent of pregnant women. Lung and kidney disease affect about 5% of people, other respiratory diseases affect 2.2 percent, and cancer, immune disorders, asthma, liver, and tuberculosis affect less than 2% of people. Conclusion: Patients with hypertension should be mindful of the risk of contracting Covid-19. Because of the extent of the losses incurred by the Covid-19 pandemic, different parties must work together to avoid and manage it.